Approaches to Daily Monitoring of the SARS-CoV-2 Outbreak in Northern Italy - Moirano, Giovenale; Richiardi, Lorenzo; Novara, Carlo; Maule, Milena (Frontiers in Public Health, 2020)
Italy was the first European country affected by the Sars-Cov-2 pandemic, with the first autochthonous case identified on Feb 21st. Specific control measures restricting social contacts were introduced by the Italian government starting from the beginning of March. In the current study we analysed public data from the four most affected Italian regions. We (i) estimated the time-varying reproduction number (R_t), the average number of secondary cases that each infected individual would infect at time t, to monitor the positive impact of restriction measures; (ii) applied the generalized logistic and the modified Richards models to describe the epidemic pattern and obtain short-term forecasts. We observed a monotonic decrease of R_t\ over time in all regions, and the peak of incident cases approximately two weeks after the implementation of the first strict containment measures. Our results show that phenomenological approaches may be useful to monitor the epidemic growth in its initial phases and suggest that costly and disruptive public health controls might have a positive impact in limiting the Sars-Cov-2 spread in Northern Italy.